MA'NA AL-TASYJĪ' FI AGNIYAH "HĀWIL MARRATAN UKHRA WAKUN FUḌŪLIYYAN WA TAṢNA' AL-MUSTAHĪL" LI HUMUUD AL-KHUḌR: DIRĀSAH SIMIUṬĪQIYYAH 'INDA FERDINAND DE SAUSSURE - Asror, Muhammad Khozinul; Yurisa, Penny Respati (Annual International Conferences on Language, Literature, and Media, 2022)
Song is one of the means of communication that is considered successful in delivering messages to the listeners. Hammoud Al-Khidr is one of the musicians who has succeeded in presenting songs filled with encouraging messages. The researchers were interested in analyzing the meaning of encouragement found in each of his songs. This research is descriptive qualitative . The data sources were the lyrics of the song “Hawil maratan 'ukhraa wakun fudulia watasnae almustahila" and YouTube. This research used the semiotic theory of Ferdinand de Saussure, which seeks to understand the meaning of a literary work using signs. The objectives of this research were to know the reference and the reference found in the songs; and uncover the meaning of encouragement found in the songs. The results of this research were: (1) What is referred to in these songs is the lyrics of the song itself, and what is referred to is the interpretation of the reference; (2) The meaning of encouragement in the song Try Again is the encouragement to try again, focus on the future, not be afraid of dreaming, renew the soul, and be dissatisfied easily. Encouragement in the song "Lilmuhawalat maratan 'ukhraa" is to encourage curiosity and to ask lots of questions and discussion. The meaning of the encouragement contained in the song "Tasnae almustahil" is the encouragement to conquer the impossible, strengthen the resolve, move together, grow, advance, trust and commit. It is expected that there will be more other researchers who explore similar topic and they are suggested to use other theories to advance this research.